CB1 cannabinoid receptor in brain mesolimbic system of mitragynine-sensitised albina wastar rats as a candidate molecular terget in mitragyna speciosa (KETUM) addiction - Mustapha, Muzaimi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2015)
Emerging new psychoactive substances impose public health implications worldwide, and include plants' phytochemicals such as Mitragynine (MG) from Mitragyna speciosa (or 'Ketum'). Studies have demonstrated the reciprocal interaction between endocannabinoid (ECB) system and opioid systems in the modulation of brain-reward and neurobiological mechanisms underlying drug addiction. To date the neurochemical basis of Ketum abuse potential remains elusive. This research attempted to implicate ECB system in the abuse liabilities of emerging psychoactive plant, Ketum and its opioid-like alkaloid, mitragynine (MG). We had demonstrated the locomotor and behavioural effects of MG-sensitised Swiss albino mice in lntelliCage® using an approach of context-independent sensitisation. Animals were later sacrificed for immunohistochemical localisation of CB1 receptor in the brain with confirmatory analysis using Western blotting of the brain homogenates. Adult Albino Swiss mice were subjected to experimental groups of MG alone; MG + NIDA- 41020 (CB1 receptor antagonist); Morphine sulphate; .0.-9-Tetrahydrocannabinol + NIDA-41020; and vehicle. Daily intraperitoneal injection (i.p) of MG (5 to 25 mg/kg; 5mg/kg increment) at a 6-day interval was administered for 30 days, and plus once daily, 20mg NIDA-41 020 (oral). Findings to date showed neuroadaptive chronic exposure of morphine, and works are in its final phase for comparison with MG and in the presence of CB1 antagonist. Data analysis to date provide supportive ground for the first time to our knowledge, to indicate the involvement of CB1 receptor as the neural target of Ketum misuse potential. (Two manuscripts in preparation for potential publication in indexed-journals).